Demand functions for agro-food products by product and household categories in Romania - Alexandri C. (Agricultural price reform under transition in Bulgaria, Romania, and Slovenia, 1998)
The objective of this paper is to estimate Engel curves, based on about fifteen food products, for three income groups, urban and agricultural households being treated separately, for the period of transition in Romania using Household Budget Survey data for the period 1991-1994. The analysis covers only food items purchased by the household, although consumption of own-produced food commodities (subsistence production) is high, in particular for some commodities (poultry meat, eggs, potatoes, apples). The estimated income elasticities are generally high. Income elasticities for total food purchases range from 0.45 (high income) to 0.70 (low income) for agricultural households and from 0.49 (high income) to 0.84 (low income) for urban households. Individual commodity elasticities range according to a priori expectations with the lowest elasticities observed for bread and the highest elasticities observed for meat and citrus fruit.